An Ethical Review of Human Existence in the Era of Artificial Intelligence: Automation, Autonomous Weapons, and the Threat of Superintelligence - Wahyu Kusuma Putra; Evy Nurmiati (Politeknik Aceh Selatan, 2026)
Artificial Intelligence (AI) has rapidly evolved into one of the most influential technologies of the twenty-first century, transforming human activities across economic, social, political, and security domains while simultaneously raising increasingly complex ethical concerns regarding human existence. This study aims to critically examine the ethical implications of AI by focusing on three interconnected domains automation, autonomous weapons, and superintelligence and to identify ethical principles capable of supporting responsible AI governance. A Critical Literature Review (CLR) was employed to synthesize peer-reviewed journal articles, conference proceedings, and internationally recognized policy documents retrieved from major academic databases and global organizations, including Scopus, IEEE Xplore, ScienceDirect, SpringerLink, ACM Digital Library, UNESCO, OECD, the European Commission, and the International Committee of the Red Cross. The findings reveal that although AI substantially enhances productivity, innovation, and decision-making capabilities, it also introduces significant ethical challenges, including workforce transformation, accountability gaps in autonomous military operations, diminished human autonomy in AI-assisted decision-making, and long-term existential risks associated with highly autonomous intelligent systems. The synthesis further demonstrates that current ethical approaches remain fragmented because they frequently address these issues independently rather than as interconnected dimensions of AI development. This study concludes that a Human-Centered Ethical Governance Framework, grounded in the principles of human dignity, human autonomy, transparency, accountability, fairness, and meaningful human oversight, provides a more comprehensive approach for governing AI technologies and ensuring that future AI development remains aligned with fundamental human values while supporting sustainable coexistence between humanity and intelligent machines.